Intra- and Interlaboratory Reproducibility of Ultra Performance Liquid Chromatography–Time-of-Flight Mass Spectrometry for Urinary Metabolic Profiling - Benton, H. Paul; Want, Elizabeth; Keun, Hector C; Amberg, Alexander; Plumb, Robert S; Goldfain-Blanc, Francoise; Walther, Bernhard; Reily, Michael D; Lindon, John C; Holmes, Elaine; Nicholson, Jeremy K; Ebbels, Timothy M. D (Analytical chemistry (Washington), 2012)
Liquid chromatography coupled to mass spectrometry (LC–MS) is a major platform in metabolic profiling but has not yet been comprehensively assessed as to its repeatability and reproducibility across multiple spectrometers and laboratories. Here we report results of a large interlaboratory reproducibility study of ultra performance (UP) LC–MS of human urine. A total of 14 stable isotope labeled standard compounds were spiked into a pooled human urine sample, which was subject to a 2- to 16-fold dilution series and run by UPLC coupled to time-of-flight MS at three different laboratories all using the same platform. In each lab, identical samples were run in two phases, separated by at least 1 week, to assess between-day reproducibility. Overall, platform reproducibility was good with median mass accuracies below 12 ppm, median retention time drifts of less than 0.73 s and coefficients of variation of intensity of less than 18% across laboratories and ionization modes. We found that the intensity response was highly linear within each run, with a median R 2 of 0.95 and 0.93 in positive and negative ionization modes. Between-day reproducibility was also high with a mean R 2 of 0.93 for a linear relationship between the intensities of ions recorded in the two phases across the laboratories and modes. Most importantly, between-lab reproducibility was excellent with median R 2 values of 0.96 and 0.98 for positive and negative ionization modes, respectively, across all pairs of laboratories. Interestingly, the three laboratories observed different amounts of adduct formation, but this did not appear to be related to reproducibility observed in each laboratory. These studies show that UPLC–MS is fit for the purpose of targeted urinary metabolite analysis but that care must be taken to optimize laboratory systems for quantitative detection due to variable adduct formation over many compound classes.